PENGGUNAAN MEDIA SMART TV DALAM MENINGKATKAN KONSENTRASI BELAJAR ANAK USIA DINI - Ocha Nabila Margareta; Imel Ariani; Zahrotul Lathifah; Eka Putri Parastika Sari; Ria Seftia Purnama; Aniawati Aniawati (Institut Agama Islam Ngawi, 2026)
This research was conducted to examine the extent to which the use of smart TV media could enhance the learning concentration of early childhood students at RA Bahrul Ulum Rebang Tangkas. Through the application of learning technology, it was expected that a more engaging learning atmosphere could be created, allowing children to become more focused while participating in learning activities. The method applied in this study was Classroom Action Research (CAR) with a descriptive qualitative approach, involving 15 children from Group B as the research subjects. Data were collected through observation, interviews, and documentation carried out throughout the learning process. In its implementation, smart TV media was used as a learning tool that displayed various educational videos, learning songs, and interactive images adapted to the theme of the ongoing activities. The use of this media assisted teachers in delivering instructional content in a more varied manner, while also capturing children's attention during learning activities. Based on the findings, there was an improvement in children's learning concentration following the implementation of smart TV media in the learning process. Children appeared more focused when paying attention to the teacher's explanations, more enthusiastic in participating in activities, and more active in responding to questions. In addition, the learning atmosphere became more enjoyable, reducing the likelihood of children feeling bored. Therefore, smart TV media can be considered an effective alternative learning medium to support the learning process of early childhood students.